Atlantic salmon ( Salmo salar L.) exposed to cultured gill-derived Neoparamoeba branchilila fail to develop amoebic gill disease (AGD) - Vincent, BN; Adams, MB; Crosbie, PBB; Nowak, BF; Morrison, RN (European Association of Fish Pathologists, 2007)
Gill-derived Neoparamoeba spp. from Atlantic salmon cause amoebic gill disease (AGD) in nave recipients. Atlantic salmon were inoculated with clonal gill-derived Neoparamoeba branchiphila that had been cultured in the presence or absence of Atlantic salmon cutaneous mucus. Neoparamoeba branchiphila did not elicit AGD and the supplementation of cultures with cutaneous mucus did not influence virulence.